Novel Biomarkers of Gastrointestinal Cancer - Shimura, Takaya (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Gastrointestinal (GI) cancer is a major cause of morbidity and mortality in the world. Since early diagnosis and optimal treatment selection are crucial to improving the prognosis of these diseases, the discovery of useful biomarkers has the potential to greatly reduce their burden. Recent technical and mechanical developments have allowed for the detection of tiny differences in various factors modified in physical conditions, which could contribute to the discovery of novel biomarkers for some diseases.In this Special Issue, we aim to focus on novel biomarkers for GI cancers, including esophageal cancer, gastric cancer, colorectal cancer, liver cancer, pancreatic cancer and biliary cancer. In addition, any samples (tissue, blood, urine and feces) are useful as biomarker sources, although body-fluid-based biomarkers are promising as diagnostic biomarkers due to their noninvasiveness. This Special Issue aims to collect novel insights clarifying the current situation and future perspective in this field.